Stock Price Performance of LQ45 Companies Before and After the 2024 General Election - Topan Lilian Napitupulu; Rahima Br Purba (Journal of Research in Social Science and Humanities, 2025)
This study examines the stock price performance of firms included in the LQ45 index before and after Indonesia’s 2024 General Election (Pemilu). A quantitative comparative event-study approach is applied using Abnormal Return (AR) and Cumulative Abnormal Return (CAR) as key metrics. The sample consists of 45 LQ45 companies listed on the Indonesia Stock Exchange. Expected returns are estimated using the Market-Adjusted Model (expected return equals market/IHSG return), with an observation window of t?3 to t?1 (pre-event) and t+1 to t+3 (post-event). Data were calculated in Microsoft Excel and statistically tested in SPSS using a normality test, Paired Sample T-Test, and Wilcoxon Signed Rank Test as a robustness check. Descriptive results indicate changes in AR patterns between the pre- and post-election periods. The Paired Sample T-Test shows that the difference is not significant at the 5% level (p = 0.079) but is marginal at the 10% level. In contrast, the Wilcoxon test reveals a significant difference at the 5% level (p = 0.024), with most stocks exhibiting lower abnormal returns after the election (32 stocks post pre). Overall, the findings suggest an asymmetric market reaction, with abnormal performance relatively stronger before the event and weakening afterward.